A tree structure for dynamic facility location - Henzinger, Monika; Leniowski, Dariusz; Mathieu, Claire (Algorithmica, 2020)
In this paper, we study the problem of dynamic facility location. We maintain a solution with cost O(1) times the cost of an optimal solution in metric spaces with bounded doubling dimension. The amortized update time is polylogarithmic in the parameters of the problem.